LEGAL REFORM: APPLICATION OF PANCASILA VALUES AND UTILITARIANISM IN ACHIEVING JUSTICE - Yeni Santi; Datumula, Sarfika; MS, Syaifullah (Adisam Publisher, 2024)
Legal reform is an effort to improve the existing legal system with the aim of realizing better justice for society. In the context of applying the values ​​of Pancasila and utilitarianism, there is an interesting approach that can provide a comprehensive view of legal reform efforts. First of all, Pancasila values ​​as the basis of the Indonesian state have moral principles that can be used as a basis for forming laws. Principles such as social justice, democracy and fair humanity can be a basis for formulating legal policies that prioritize the interests of society as a whole. Meanwhile, the utilitarianism approach which emphasizes the concept of as much happiness or well-being as possible for as many people as possible can also be an important consideration. in legal reform. By taking into account the impact of a legal policy on the welfare of society at large, the application of utilitarianism can help assess the effectiveness and justice of a legal regulation. This can be reflected in efforts to create legal policies that are not only based on moral values, but also take into account positive consequences for society as a whole. Thus, the application of Pancasila values ​​and utilitarianism in legal reform can be a strong foundation in realizing better justice for all Indonesian society.